How to Calculate Fertigation Injection Rates for Commercial Blueberry Production - Guodong Liu; Jeffrey Williamson; Gary England; Alicia Whidden (EDIS)
To increase nutrient and water use efficiencies and reduce nutrient leaching and environmental concerns, fertigation is recommended for commercial blueberry production. In fact, successful fertigation can enhance sustainability and maximize profitability for commercial blueberry enterprises. One of the key factors in fertigation is the correct calculation of fertilizer injection rate and time for the acreage. This publication helps blueberry growers correctly calculate fertigation injection rates and times and provides reference tables for checking injection rates and times needed for a variety of production scenarios. This 3-page fact sheet was written by Guodong Liu, Jeffrey Williamson, Gary England, and Alicia Whidden, and published by the UF Department of Horticultural Sciences, March 2012.